Александр Суворов: ист. повесть / С. Т. Григорьев - Григорьев Сергей Тимофеевич (Военная библиотека школьника, 1980)
Экземпляры: аб ДБ (1980) / Инвентарный номер: 63715 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Г 83 / ББК: 84(2Рос=Рус)6